Disturbances of functional condition of pro-oxidant and antioxidant systems in guinea pigs’ lungs in experimental allergic alveolitis - Mariana Ljubomurivna Baida (Journal of Education, Health and Sport, 2017)
We have analyzed the results of experimental work of alterations in indices of pro-oxidant (conjugated diene and malondialdehyde) and antioxidant (superoxide dismutase, catalase) systems in guinea pigs’ lungs in experimental allergic alveolitis. The results of investigation showed that a significant increase in conjugated diene level in animals’ lungs was observed at all stages of experimental allergic alveolitis development under the conditions of immobilization stress as compared with control group, indicating activation of this marker.